PENYULUHAN METODE AUDIO VISUAL DAN DEMONSTRASI TERHADAP PENGETAHUAN MENYIKAT GIGI PADA ANAK SEKOLAH DASAR - Prasko Prasko; Bedjo Santoso; Bambang Sutomo (Jurnal Kesehatan Gigi, 2016)
TITLEEducation with audio-visual and modeling methods to tooth brushing education in elementary school childrenABSTRACTThe maintenance of oral health as well as health coaching teeth, especially in children of school groups need special attention because at this age children are undergoing the process of growth and development. Previous dental state will affect the development of dental health in adulthood. Through training programs is expected to increase knowledge and raise awareness of the importance of maintaining oral health and able to participate actively in increasing efforts to maintain self. The purpose of this research was to determine the effectiveness of extension methods and audio visual demonstration of the knowledge brushing teeth.This research uses descriptive quantitative method is a method of research conducted with the main objective to create a picture or a description of a situation in an objective that has to do with the problems examined. The instrument used was the questionnaire.From the results of the study conducted by researchers in the field to the students of class V and VI Elementary School Pedalangan 02 Semarang is known that after counseling with the demonstration of the results obtained knowledge of students of class V in both categories with a score of 7 and after counseling with audio visual results obtained knowledge graders VI enter both categories with a value 6.95. It can be concluded that the extension demonstration and extension with audio visual effective for use in improving the knowledge toothbrushing on elementary school children.Key words : Counseling method of demonstration and audio visual, knowledge of  brushing teeth